Understanding the Perceptions of Asian University Students Toward Thai Tourism Destinations: The Cases of Phuket and Pattaya - Kanyika Shaw; Nutthapon Jitprapai; Jantima Kheokao (Asian Journal for Public Opinion Research)
This study investigates Asian university students’ perceptions of Phuket and Pattaya, emphasizing city image, defining attributes, information exposure, familiarity, and travel intentions. Using a quantitative survey with 3,432 online respondents, the study reveals that Phuket consistently outperforms Pattaya across four dimensions. Tourism and recreation findings show Phuket as more vibrant and diverse in activities. In authenticity and atmosphere, Phuket is slightly favored for its friendliness and cleanliness. Both cities score similarly in economic factors, with Phuket being slightly more navigable. In environmental and safety factors, Phuket is viewed as safer and more climate-friendly, though both cities are crowded. Path analysis was utilized to investigate the relationship between information exposure, familiarity, and visitation intentions. The findings reveal that information exposure significantly affects visitation intentions, both directly and indirectly, with familiarity serving as a critical mediator. Increased information exposure enhances familiarity, which, in turn, strengthens the intention to visit the cities. To elevate destination appeal, recommendations include targeted marketing via diverse media, highlighting authentic experiences, and addressing safety and authenticity concerns. These strategies can enhance Phuket and Pattaya's competitive edge in tourism.